Eurocentric roadblocks to school change in Nunavut - Berger, Paul (Études/Inuit/Studies, 2009)
Sixty years after its inception, schooling in the eastern Arctic remains predominantly based on Euro-Canadian values, curricula and pedagogy, and privileging English over Inuit languages. Many studies have linked this model of schooling to poor academic achievement and assault on Inuit culture, and many Inuit have for decades indicated that they want schooling to reflect Inuit culture. In this article I argue that Eurocentrism continues to slow the pace of educational change in Nunavut, despite the supportive proclamations and good intentions of White teachers and bureaucrats. Based on fieldwork in one Nunavut community and on observations as a teacher and visitor in Arctic areas, I present examples of individual Eurocentrism, Eurocentrism embedded in the educational system, and pan-Canadian Eurocentrism that create roadblocks to school change in Nunavut. I also suggest some ways to challenge the roadblocks. As Inuit continue to press for schools based on Inuit priorities Euro-Canadians should act as allies. To this end, Euro-Canadians need to acknowledge and challenge Eurocentrism.